Validation of the virus teaching module based on project based learning on creative thinking ability - Aminuddin Prahatama Putra; Muhammad Zaini; Mella Mutika Sari (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
The virus teaching module based on project based learning (PjBL) was developed as an innovative learning medium and is expected to accommodate students' learning needs to improve their creative thinking abilities. This research aims to validate the PjBL-based virus teaching module for valid creative thinking abilities. This research uses a four-D (4D) research and development model but only reaches the product validity stage. Validation was carried out by two validators, namely experts in the field of biology, especially regarding viruses, and education experts. The instrument used is a validity sheet which includes aspects of suitability of content, grammar, sentences with indicators of creative thinking abilities. Data were analyzed using quantitative descriptive techniques with a Likert scale resulting from validation carried out by the validator. The research results show that the average open module validity score is 3.3 with a very valid category. Therefore, the project-based learning module based on the teaching virus that was developed is very valid and can be used to train the creative thinking of class X SMA/MA students. This research needs to be followed up by continuing the implementation of broader research to prove how practical and effective the PjBL-based virus teaching module is when used by students in learning.Abstrak Modul ajar virus berbasis project based learning (PjBL) dikembangkan sebagai media pembelajaran yang inovatif dan diharapkan dapat mengakomodasi kebutuhan belajar peserta didik untuk meningkatkan kemampuan berpikir kreatif. Penelitian ini bertujuan untuk memvalidasi modul ajar virus berbasis PjBL terhadap kemampuan berpikir kreatif yang valid. Penelitian ini menggunakan model penelitian dan pengembangan four-D models (4D) namun hanya sampai pada tahap validitas produk. Validasi dilakukan oleh dua orang validator yaitu pakar dalam bidang biologi khususnya mengenai virus dan pakar pendidikan. Instrumen yang digunakan berupa lembar validitas yang meliputi aspek kesesuaian isi, tata bahasa, kalimat dengan indikator kemampuan berpikir kreatif. Data dianalisis menggunakan teknik deskriptif kuantitatif dengan skala Likert hasil validasi yang dilakukan oleh validator. Hasil penelitian menunjukkan skor rata-rata validitas modul ajar sebesar 3,3 dengan kategori sangat valid. Oleh karena itu, modul ajar virus berbasis project based learning  yang dikembangkan sangat valid dan dapat digunakan untuk melatih berpikir kreatif peserta didik kelas X SMA/MA. Penelitian ini perlu ditindaklanjuti dengan melanjutkan penelitian implementasi yang lebih luas untuk membuktikan seberapa praktis dan efektif modul ajar virus berbasis PjBL saat digunakan oleh peserta didik dalam pembelajaran.